Design and Simulation of High-Sensitivity AlGaN/GaN Based MOS-HEMT Biosensor for Biomolecule Detection - Kumar, Rakesh; Chandan, Bandi Venkata; Nigam, Kaushal Kumar; Kumar, Ashish; Tanveer, Adil; Kumar, Hitesh (International Conference on Signal Processing and Communication (Online), 2025)
This work reports a simulation and analysis of the electrical properties of the Metal-Oxide-Semiconductor High Electron Mobility Transistor (MOS-HEMT) utilized as a biosensor. A cavity is incorporated on the drain side of the MOS-HEMT for bio-sensing applications. The gate-to-source distance is considered smaller than the gate-to-drain distance to enhance the sensitivity. The impacts of charged and neutral biomolecules on the electrical properties, such as drain current and threshold voltage sensitivity, are thoroughly examined. An increase in the dielectric constant leads to a decrease in the drain current, while an increase in the positive charge of biomolecules increases the drain current. The maximum observed shifts are -3.45 V in threshold voltage and 40.99 mA/mm in drain current for neutral keratin biomolecules. Similarly, for a charged biomolecule with a charge density of 3×10 12 , a shift of 0.8 V in threshold voltage and -25 mA/mm in drain current was recorded. The structural analysis of the MOS-HEMT biosensor uses Silvaco ATLAS software, providing insights into its performance in detecting biomolecules.